2021
DOI: 10.3390/ijerph18041410
|View full text |Cite
|
Sign up to set email alerts
|

Engagement in Health Risk Behaviours before and during the COVID-19 Pandemic in German University Students: Results of a Cross-Sectional Study

Abstract: Tobacco and cannabis use, alcohol consumption and inactivity are health risk behaviors (HRB) of crucial importance for health and wellbeing. The impact of the COVID-19 pandemic on university students’ engagement in HRB has yet received limited attention. We investigated whether HRB changed during the COVID-19 pandemic, assessed factors associated with change and profiles of HRB changes in university students. A web-based survey was conducted in May 2020, including 5021 students of four German universities (69%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
84
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 55 publications
17
84
2
4
Order By: Relevance
“…We found associations between changes in all analysed health behaviours (smoking, alcohol drinking, and physical activity) and speci c person characteristics, such as higher age, lower education level, and higher net household income. Comparable associations have also been found by other international research groups [28, 29,31,43]. As previous studies suggested, aspects such as stress, boredom and anxiety seem to negatively in uence health behaviour change during country-speci c COVID-19 restrictions [27,28,30,31,43].…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…We found associations between changes in all analysed health behaviours (smoking, alcohol drinking, and physical activity) and speci c person characteristics, such as higher age, lower education level, and higher net household income. Comparable associations have also been found by other international research groups [28, 29,31,43]. As previous studies suggested, aspects such as stress, boredom and anxiety seem to negatively in uence health behaviour change during country-speci c COVID-19 restrictions [27,28,30,31,43].…”
Section: Discussionsupporting
confidence: 60%
“…Current studies report heterogeneous results about the change in smoking, drinking behaviour, and physical activity [27][28][29][30][31][32][33][34][43][44][45]. Many of these studies were conducted as online surveys, and data were reported as being not representative for the general population of the respective countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of the larger C19 ISWS, the online survey was conducted at four German universities in May 2020; participants included 5,021 students, approximately two-thirds of the sample came from the University of Bremen and the University of Siegen and the other third constituted students from the Charité—Universitätsmedizin Berlin and the Heinrich Heine University Duesseldorf ( 15 ). Students were predominantly invited to participate in the study via email and on the universities' homepages, as well as e-learning platforms.…”
Section: Methodsmentioning
confidence: 99%
“…In Europe, a study of German young adults demonstrated that 24.4% reported a decrease in binge drinking while 5.4% reported an increase (Busse et al, 2021). These results suggest a rough estimate of the relative proportion of the young adult population who may respond to the pandemic consistent with either the Availability and Stress and Coping hypotheses.…”
Section: Changes In Alcohol Use During the Covid-19 Health Emergencymentioning
confidence: 89%